The Influence of the Internalization of Religious Values and the Pesantren Lifestyle on the Control of Consumptive Behavior among Muslim University Students in Surabaya - Sholeha, Sofia Imroatus; Anwar, Moch. Khoirul (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to analyze the influence of the internalization of religious values and the pesantren lifestyle on the control of consumptive behavior among Muslim university students in Surabaya. The research uses an associative quantitative approach with primary data collected through an online questionnaire. The sample consists of 153 respondents selected using purposive sampling from various universities in Surabaya. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 23. The results show that the internalization of religious values has a significant and negative effect on consumptive behavior (t = -3.363; sig. = 0.001), meaning that the higher the internalization of religious values, the lower the studentsâ€™ consumptive behavior. Meanwhile, the pesantren lifestyle does not have a significant partial effect (t = -1.349; sig. = 0.179). However, simultaneously, both variables have a significant effect on consumptive behavior (F = 15.728; sig. 0.000) with a contribution of 17.3% (RÂ² = 0.173). These findings imply that strengthening the continuous internalization of Islamic values is an important strategy in shaping moderate and responsible consumption patterns among Muslim students with pesantren backgrounds.